Telemedicine: the experience of health professionals in the supplementary sector - Araújo, Heloísa Pimenta Arruda [UNESP]; dos Santos, Lucas Cardoso; Alencar, Rúbia Aguiar [UNESP] (FapUNIFESP (SciELO), 2023)
Objective: To know the experience of health care professionals about telemedicine in a supplementary health service. Method: This is a qualitative study carried out in a health clinic in the city of São Paulo with 12 participants selected through intentional sampling. Data collection took place through semi-structured interviews and data processing followed the methodological framework of Bardin content analysis. Results: The speeches that emerged addressed telemedicine in the context of professional training, the care modalities carried out through digital technologies, the benefits and challenges identified in the practice of telemedicine for work and care processes. Conclusion: The need for public policies and training was identified, aimed at improving understanding of digital health, its modalities and potential in care, teaching and research environments and in health organizations, aligned with training for the use of telemedicine as the one that qualifies the care provided by health professionals.
Telesalud: la experiencia de dos profesionales de la salud en un sector complementario
Telessaúde: a experiência dos profissionais de saúde no setor suplementar
Keywords: Qualitative Research; Supplemental Health; Telemedicine